Perineal Sigmoidectomy for Prolapse of a Side-to-End Handsewn Coloanal Anastomosis. Issue 5 (May 2016) - Clipet, Fabien; Sabbagh, Charles; Regimbeau, Jean-Marc
Abstract : Supplemental Digital Content is available in the text.